Community‐acquired Legionnaires' disease in a renal transplant recipient with unclear incubation period: the importance of molecular typing. Issue 5 (26th September 2015) - Cassier, P.; Bénet, T.; Nicolle, M.C.; Brunet, M.; Buron, F.; Morelon, E.; Béraud, L.; Descours, G.; Jarraud, S.; Vanhems, P.
Abstract Transplant recipients are at risk of developing Legionnaires' disease (LD) because of impaired cellular immunity. Here, we describe a renal transplant recipient who developed LD at least 10 days after hospital admission and transplantation. The hospital water network was initially suspected, but further testing determined that the probable source was the patient's domestic water supply. Our report also suggests that the patient's immunosuppressed state may have switched potential colonization to pneumonia.